Towards a Pluralistic Account of Thought Experiments. - Frappier, Mélanie (Philosophia, 2024)
In light of our knowledge about neurodiversity, I argue that the cognitive science framework Miščević uses in Thought Experiments must be broaden to create a pluralistic account of thought experimentation, one able to account for the many ways thought experiments are replicated using not only visual models, but also arguments, conceptual analyses, and images as some of the many instruments used in the laboratory of our mind.